PELAKSANAAN TUGAS RECEPTIONIST DI SIJORI RESORT AND SPA BATAM - Busni, Hany Mutia; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Respon in the world of tourism is the opinion of way of view of visitors and tourists in understanding a tourist destination. This research was conducted in Sijori Resort & SPA Batam on Ir. Sutami street No.06, Sungai Harapan, Sekupang- Batam, kepulauan riau- indonesia. this study aims to determine the response of visitors to the implementation of recxeptionist duties in batam sijori resort and spa. this research uses quantitative descriptive method to process the data obtained in the field through interviews, observations and questionnaires. all the information collected and studied to become a unified whole (Sugono 2000). As for the sample in research 100 respondent. The determinantion of respondents with accidental sampling. Data collection techniques used are observations, interviews, questionnaires, using Likert scale as a measuring tool. Based on the results of research that has been done the implementation of recxeptionist duties in batam sijori resort and spa with sub variable the main fungsion , duties and responsibilities with good research conclusions.Â Keywords :Respon Of Visitors, Resort and Recepcionist